Effect of tooth discoloration severity on the efficacy and color stability of two different trayless at-home bleaching systems - R. Banu Ermis; Esra Uzer CELIK; Gul YILDIZ; Basak YAZKAN (Tabriz University of Medical Sciences, 2018)
Background. The use of trayless at-home bleaching agents in darker teeth has raised some concerns due to their unknown efficacy. The aim of this in vitro study was to evaluate the effect of tooth discoloration severity on the efficacy and color stability of two different trayless at-home bleaching systems. Methods. Ninety enamel‒dentin samples were divided into two groups: lighter and darker teeth. The teeth in each group were further divided into three groups (n=15): (1) tray-based system with 10% carbamide peroxide (Opalescence Oh) (control group); (2) a tray-applied whitening membrane with 10% hydrogen peroxide (Treswhite Supreme); and (3) a whitening pen with 22% carbamide peroxide (Hollywood Smiles). After bleaching, the teeth were stained for 9 days using red wine. Color readings before bleaching treatment were carried out using a dental spectrophotometer and were repeated 24 h after bleaching treatment and 24 h after staining process. ANOVA, Bonferroni and Dunnett C tests were used at 5% significance level. Results. No differences were observed between the bleaching efficacy of Treswhite Supreme and Opalescence Oh in the lighter teeth, while Opalescence Oh exhibited the best bleaching efficacy in the darker teeth (P<0.05). Hollywood Smiles exhibited the worst bleaching efficacy but the best color stability in both lighter and darker teeth (P<0.05). No differences were observed between the color stability values of Treswhite Supreme and Opalescence Oh. Conclusion. This study suggested that both the tooth discoloration severity and the type of trayless system used affected the bleaching efficacy, whereas only the type of trayless system affected the color stability.